Learning Outcomes of Islamic Education and Character Building: How Effective Is the Aptitude-Treatment Interaction (ATI) Model? - Suci Amellia; Baharudin; Deden Makbuloh; Saputra, M. Indra (Tadris: Jurnal Keguruan dan Ilmu Tarbiyah, 2026)
This study examines the pedagogical value of the Aptitude–Treatment Interaction (ATI) learning model in supporting higher-order evaluative thinking skills (C5) within Islamic Religious Education (IRE). A quantitative quasi-experimental design with a posttest-only control group was employed to compare learning outcomes between students taught using the ATI model and those taught through a conventional expository approach at SMP Negeri 21 Bandar Lampung. Data were analyzed using an independent sample t-test. The results indicated no statistically significant difference in evaluative learning outcomes between the experimental and control groups (p = 0.279). Nevertheless, classroom implementation revealed that the ATI model enhanced student engagement, participation, and motivation by aligning instructional treatments with students’ aptitude levels. These findings suggest that the instructional benefits of ATI may not be fully reflected through outcome-based statistical comparisons alone, particularly when assessing complex cognitive processes such as evaluative thinking. The theoretical contribution of this study lies in extending the ATI framework to higher-order cognitive assessment (C5) within IRE, an area that has received limited empirical attention. Rather than functioning solely as an outcome-enhancing model, ATI is positioned as an adaptive instructional mechanism that supports differentiated learning processes and meaningful engagement in value-oriented subjects.